2022
DOI: 10.57604/prrs-001
|View full text |Cite
|
Sign up to set email alerts
|

Common Peroneal Nerve Injuries at the Knee: Outcomes of Nerve Repair

Abstract: This is an open access article distributed in accordance with the CC-BY-NC-ND (Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International) license. The article can be used by giving appropriate credit and mentioning the license, but only for non-commercial purposes and only in the original version. For further information: https://creativecommons.org/licenses/by-nc-nd/4.0/deed.en

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Nerve block techniques, performed with the use of ultrasound, improve postoperative pain control and reduce opioid administration and relative side effects as vomiting and immunological impairment 14,15 . More over a recent study, demonstrated the correlation between opioid receptor and breast cancer cells migration and thus metastatization or recurrence 16,17 . All these strategies were managed to minimize delays for cancer patients due to COVID-19 by prioritizing selected cases, while non-urgent surgical procedures were postponed and waiting lists for benign diseases grew longer [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Nerve block techniques, performed with the use of ultrasound, improve postoperative pain control and reduce opioid administration and relative side effects as vomiting and immunological impairment 14,15 . More over a recent study, demonstrated the correlation between opioid receptor and breast cancer cells migration and thus metastatization or recurrence 16,17 . All these strategies were managed to minimize delays for cancer patients due to COVID-19 by prioritizing selected cases, while non-urgent surgical procedures were postponed and waiting lists for benign diseases grew longer [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Free flaps like ALT or DIEP flap, provide a proper amount of well vascularized tissues and are usually considered a valid alternative 31 . As reported by Tukiainen E., the general conditions of the patient represent a relevant element during the flap selection process, since the advantages of free flaps reconstruction should outweigh the disadvantages like longer operative time and potential thrombotic problems 32,33 . Unfortunately, in our patient a microvascular procedure was not recommended, making this reconstructive option inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of the surgical treatment was to achieve a prompt wound closure and the infection solving. Finally, as regards the postraumatic deficit of left foot dorsiflection and sensation, no treatment was started, since the closed nature of trauma, which was responsible of the possible underlying neurapraxya and the spontaneous improvement occurred within 3-4 month 24 . which spontaneously resolved during hospitalization.…”
Section: Discussionmentioning
confidence: 99%